Thermodynamic modeling of high-temperature combined cycle for hydrogen and electricity co-production - Dudek, Michał; Jaszczur, Marek; Kolenda, Zygmunt; Polepszyc, Inga (Computer Assisted Methods in Engineering and Science, 2017)
The high (HTGR) and very high (VHTR) temperature nuclear reactors are the most innovative designs and belong to the most advanced fourth generation gas-cooled reactor technology. These types of reactors are designed to have an outlet temperature between 800-1000° C for the HTGR and the VHTR respectively. Such systems are able to generate electrical energy and supply process heat in a broad spectrum of high-temperature and energy-intensive non-electric and thermal processes. In this paper, a numerical analysis of the high temperature HTGR/VHTR combined cycle with co-production of hydrogen and electricity is conducted. The presented cycle consists of three subsidiary circuits with gas turbine and two steam turbines for electric energy generation, and two heat exchangers for hydrogen production at high or medium temperature. The results show that such a combination allows a significant increase of thermal efficiency to about 50% at the reactor outlet temperature of 1273 K and a decrease in cost of hydrogen production.